Complement resistance of Borrelia burgdorferi correlates with the expression of BbCRASP-1, a novel linear plasmid-encoded surface protein that interacts with human factor H and FHL-1 and is unrelated to Erp proteins - Kraiczy, Peter; Hellwage, Jens; Skerka, Christine; Becker, Heiko; Kirschfink, Michael; Simon, Markus M.; Brade, Volker; Zipfel, Peter F.; Wallich, Reinhard (The journal of biological chemistry, 2004)
The etiologic agent of Lyme disease, Borrelia burgdorferi, is capable of circumventing the immune defense of a variety of potential vertebrate hosts. Previous work has shown that interaction of host-derived complement regulators, factor H and factor H-like protein 1 (FHL-1), with up to five complement regulator-acquiring surface proteins (CRASPs) expressed by resistant B. burgdorferi sensu lato isolates conferred complement resistance. In addition expression of CRASP-1 is directly correlated with complement resistance of Borrelia species. This work describes the functional characterization of BbCRASP-1 as the dominant factor H and FHL-1-binding protein of B. burgdorferi. The corresponding gene, zs7.a68, is located on the linear plasmid lp54 and is different from factor H-binding Erp proteins that are encoded by genes localized on circular plasmids (cp32). Deletion mutants of BbCRASP-1 were generated, and a high affinity binding site for factor H and FHL-1 was mapped to the C terminus of BbCRASP-1. Similarly, the predominant binding site of factor H and FHL-1 was localized to the short consensus repeat 7. Factor H and FHL-1 maintain their cofactor activity for factor I-mediated C3b inactivation when bound to BbCRASP-1, and factor H is up to 6-fold more efficient in mediating C3b conversion than FHL-1. In conclusion, BbCRASP-1 (i). binds the host complement regulators factor H and FHL-1 with high affinity, (ii). is the key molecule of the complement resistance of spirochetes, and (iii). is distinct from the Erp protein family. Thus, BbCRASP-1 most likely contributes to persistence of B. burgdorferi and to pathogenesis of Lyme disease.
Gesehen am 22.02.2021